Pengaruh Kualitas Kerja, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo - Erine Erlithasari; Vera Firdaus; Sumartik Sumartik (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of work quality, work environment, and work discipline on employee performance at the Population and Civil Registration Office of Sidoarjo Regency. This study uses a saturated sample, meaning that all 100 employees at the Population and Civil Registration Office of Sidoarjo Regency were used as research samples. The data collection technique was carried out using a proportional sampling technique. Data were collected through questionnaires and then analyzed using multiple linear regression. The results of this study revealed that simultaneously and partially there was a positive and significant influence between the variables of work quality, work environment, and work discipline on employee performance at the Population and Civil Registration Office of Sidoarjo Regency.